Habeas Corpus Litigation in United States District Courts: An Empirical Study, 2000-2006 - King, Nancy J. ([Verlag nicht ermittelbar], 2013)
The purpose of the Habeas Corpus Litigation in United States District Courts: An Empirical Study, 2007 is to provide empirical information about habeas corpus cases filed by state prisoners in United States District Courts under the Antiterrorism and Effective Death Penalty Act of 1996 (AEDPA). The writ of habeas corpus is a remedy regulated by statute and available in federal court to persons "in custody in violation of the Constitution..." When a federal court grants a writ of habeas corpus, it orders the state court to release the prisoner, or to repeat the trial, sentencing, or other proceeding that led to the prisoner's custody. Each year, state prisoners file between 16,000 and 18,000 cases seeking habeas corpus relief. The study was the first to collect empirical information about this litigation, a decade after AEDPA was passed. It sought to shed light upon an otherwise unexplored area of habeas corpus law by looking at samples of capital and non-capital cases and describing the court processing and general demographic information of these cases in detail. AEDPA changed habeas law by: Establishing a 1-year statute of limitation for filing a federal habeas petition, which begins when appeal of the state judgment is complete, and is tolled during "properly filed" state post-conviction proceedings; Authorizing federal judges to deny on the merits any claim that a petitioner failed to exhaust in state court; Prohibiting a federal court from holding an evidentiary hearing when the petitioner failed to develop the facts in state court, except in limited circumstances; Barring successive petitions, except in limited circumstances; and Mandating a new standard of review for evaluating state court determinations of fact and applications of constitutional law. The information found within this study is for policymakers who design or assess changes in habeas law, for litigants and courts who address the scope and meaning of the habeas statutes, and for researchers who seek information concerning the processing of habeas petitions in federal courts. Descriptive findings are provided detailing petitioner demographics, state proceedings, representation of petitioner in federal court, petitions, type of proceeding challenged, claims raised, intermediate orders, litigation steps, processing time, non-merits dispositions and merits disposition for both capital and non-capital cases which lead into the comparative and explanatory findings that provide information on current and past habeas litigation and how it has been effected by the Antiterrorism and Effective Death Penalty Act of 1996.